Structural analysis of a fault in South-West Greenland - Henriksen, Niels (Meddelelser om Grønland, 1960)
Detailed analysis has shown the step-wise development of a WNW-ESE trending wrench fault, the Laksenæs fault, in the Ivigtut area of SW Greenland. The fault has a total horizontal displacement of 6 km, with sinistral movement, and a vertical displacement of approximately 2 km. The horizontal displacement can be shown to have taken place in three successive stages, each of which occurred in a different geological period. The first horizontal displacement of 1.5 km took place in the Ketilidian and/or early Kuanitic periods and was followed by a displacement of 1.5 km in the Sanerutian period and 3 km in the Gardar period. Vertical displacement took place only with the first two stages of horizontal displacement. The Laksenæs fault is cut by a system of NNW trending dykes which have been provisionally ascribed to the Tertiary.